Because you love to hate me : 13 tales of villainy - Ameriie (2017)
A collection of classic fairy tales and stories, from Medusa to Sherlock Holmes, retold from the villains' points of view by teams of authors and "BookTubers."
Introduction / by Ameriie -- The blood of Imuriv / t Beautiful venom / by Cindy Pon -- Without the evil in the world, how do we see the good? / by Benjamin Alderson -- Death knell / by Victoria Schwab -- Dear Death / by Jesse George -- Marigold / by Samantha Shannon -- Evil revealed / by Regan Perusse -- You, you, it's all about you / by Adam Silvera -- Behind the villain's mask / by Catriona Feeny -- Julian breaks every rule / by Andrew Smith -- Julian Powell: teen psycho extraordinaire / by Raeleen Lemay -- Indigo and shade / by April Genevieve Tucholke -- Glamorized recovery: expectations vs. reality / by Whitney Atkinson -- Sera / by Nicola Yoon -- The Bad Girls' Guide to Villainy / by Steph Sinclair and Kat Kennedy.
Keywords: Villains in literature -- Fiction; Good and evil -- Fiction; Short stories; JUVENILE FICTION / Short Stories; JUVENILE FICTION / Social Issues / General (see also headings under Family).; JUVENILE FICTION / Love & Romance; Good and evil; Villains in literature; Short stories; Fairy tales; JUVENILE FICTION / Social Issues / General (see also headings under Family.).; JUVENILE FICTION / Short Stories; Fairy tales; Fantasy fiction; Fiction; Short stories; Short stories; Fairy tales; Fantasy fiction